The making of a libray: the academic library in transition, de R. S. Taylor - Macedo, Vera Amália Amarante (Revista de Biblioteconomia de Brasília, 1974)
TAYLOR, R.S. The making of a library: the academic library in transition. New York: Becker and Hayes, 1972. 250p.